Urinary tract infections in patients undergoing radical cystectomy and urinary diversion: challenges and considerations in antibiotic prophylaxis - Symeonidis, Evangelos N.; Falagas, Matthew E.; Dimitriadis, Fotios (Translational Andrology and Urology, 2019)
Radical cystectomy represents the standard of care for muscle-invasive bladder cancer. Different surgical techniques of urinary diversion have been advocated during the last years. The three primary techniques of substituting the excised bladder include the non-continent urinary diversions, the continent non-orthotopic urinary diversions, and the orthotopic urinary diversions (1). While the non-continent forms have been traditionally used, continent diversions have started gaining ground in high case volume hospitals (2). When compared to the non-continent diversions, orthotopic ones confer various advantages such as a resemblance to the native bladder, enhanced functional outcomes, less psychological burden, and better quality of life (2).